Use of stable isotopes to distinguish wild from pen‐raised northern bobwhite - Paul M. Castelli; Lisa M. Reed (Wildlife Society Bulletin)
ABSTRACT Stocking pen‐raised northern bobwhite (Colinus virginianus) into habitats inhabited by wild bobwhite is a widespread practice, yet no technique other than marking exists to distinguish between these birds when they are harvested or recaptured. We assessed the potential of stable isotope analysis of primary feather tissue to distinguish between wild and pen‐raised bobwhite. We obtained 104 feather samples from 3 game farms and 3 hunters in New Jersey, USA, collected between 1998 and 2006. We analyzed all samples for isotopes of carbon13C/12C, nitrogen15N/14N, sulfur34S/32S, and a preliminary sample for hydrogen2H/1H. Combinations of isotopic ratios of carbon, nitrogen, and sulfur yielded unique patterns for the 2 groups, enabling us to form a significant function that discriminated between these groups 100% of the time. The function was influenced most by the isotopic ratios of nitrogen and carbon. We were unable to discriminate between age classes or sex within groups, but could discriminate among farms and between years for the one farm where we had 2 years of samples. In our pilot study, stable isotope analysis of primary feather tissue was a reliable technique for distinguishing wild and pen‐raised bobwhite for 12–14 months following postjuvenal or postnuptial feather molt. Summer stocking, feeding stations, or long‐term survival of pen‐raised birds would reduce the efficacy of this technique, depending upon the definition of a wild population. © 2017 The Wildlife Society.